Understanding the county-level relationship between population change and ecological environment quality dynamic in China, 2000–2020 - Zhong, Mingxing; Liu, Qingqing; Hu, Xinyue (Frontiers in Environmental Science, 2025)
Global population growth has increasingly intensified human interferences with natural ecosystems. These interferences often exhibit complexity and diversity characteristics. Understanding the relationship between population growth and environmental issues has become a focus in the current scientific community. This study, leveraging multi-source remote sensing and census data from China for the years 2000, 2010, and 2020, utilized multiple spatial econometric models to investigate the pressure of population dynamics on Ecological Environment Quality (EEQ). A bivariate local spatial autocorrelation model was applied to pinpoint regions that experienced significant population pressure in China over the past two decades. Results showed that there was a rise in population density, with larger cities attracting more migrants to become residents and EEQ declining in most counties. The analysis revealed a strong spatial dependence between changes in EEQ and population. Spatial regression models were more effective than non-spatial models in explaining population pressure on EEQ. Population growth was significantly associated with EEQ decline. Based on the spatial regression model, EEQ decreased by 0.029% for every 1% increase in population from 2000 to 2010. During 2010–2020, this impact was more pronounced, with a 1% population associated with a 0.069% decline in EEQ. Pressure zones analysis showed the most widespread regions were unsustainable zones (decreases in population and EEQ), followed by areas with both population increases and EEQ declines, with fewer regions demonstrating coordinated development improvements. Effective solutions to address the challenges of population pressure on EEQ involve government regulation, strategic planning, cross-regional management, and the sharing of responsibilities and benefits.